Vertical graphene nanowalls coating of copper current collector for enhancing rate performance of graphite anode of Li ion battery: The merit of optimized interface architecture. (1st April 2018) - Liu, Xiaofei; Wang, Dong; Zhang, Bingsen; Luan, Chen; Qin, Tingting; Zhang, Wei; Wang, Duo; Shi, Xiaoyuan; Deng, Ting; Zheng, Weitao
Abstract: Carbon coating has been attracting wide interests as optimum protection technology for Li ion batteries. Recently, carbon-coating has been considered as effective modification for copper/aluminum current collector. Although rate performance and lifetime of electrodes have been widely investigated, interfacial insight remains very superficial, hampering considerable improvement of electrode performance. Here we propose mechanistic models of double interfaces: one interface locates between Cu and active materials, and the other is referred to as solid electrolyte interphase (SEI) film coating on the current collector. Then vertical graphene nanowalls coated copper (VG) was prepared to reduce interfacial resistance of SEI film derived from an amorphous carbon coating layer. As a result, it exhibited a good rate performance with ∼190 mAh/g at 3 C, in contrast with ∼160 mAh/g for commercial carbon-coated copper (CC) and ∼90 mAh/g for traditional bare copper (BC). Graphical abstract: Highlights: The synthesized uniformly vertical graphene nanowalls are coated on copper current collector. The wetting performance of current collector with active materials highly affects rate performance. Graphene coating affords stable and low resistance of SEI film for excellent rate performance of Li ion battery.